Implementation Of Islamic Economic Principles in Household Financial Management (Analysis of Expenditure and Financing Patterns) - Nurlinda Yunus; Rahmatia J. Lopuo; Heldy Vanni Alam (Global Scientific Publishing, 2023)
The aim of this study For Review Principles of Islamic Economics in Managing Household Finances ( in pattern expenses and financing ). Study This use method study Descriptive Qualitative . Focus (indicator ) research is 1 .) explains implementation principle economy in management finance House ladder. 2.) knowing constraint what the house faces ladder in management finance family ? 3.) explain pattern expenditure and financing in management finance. Research result show that Implementation Principles of Islamic Economics in Home Financial Management ladder seen through objectives and benefits in a way direct nor No direct ie For make House ladder more blessed by Allah SWT at once can make House ladder more Sakinah Mawaddah Warahmah . Impact Positive in implementation Principle Islamic economics between others: 1) relationship House ladder become Sakinah Mawaddah Warahmah , 2) Increase your sense of caring to fellow people God's creation , 3) Life is more blessings and 4) Increase motivation unique more Lots giving alms , infaq and zakat because as much as possible treasure just deposit from Allah SWT. After study Implementation Principles of Islamic Economics in Managing Household Finances ( Analysis of Expenditure and Financing Patterns ) .
Keywords: Principles of Islamic Economics; Households; Patterns